Age, inequality and the public provision of healthcare - Anirban Mitra (University of Kent, School of Economics, 2021)
How does economic inequality affect public spending on healthcare in democracies? Does this depend upon the demographic composition of the electorate? We build a multidimensional model of political decision-making with endogenous political parties to analyse such questions. Voters in our model differ in terms of income and age. The tax rate, the allocation of the revenue between income redistribution and two forms of public spending - healthcare and capital investment - are determined through political competition. All agents value healthcare equally but the young like capital investment more than the old do. We find that when the young are a majority, public healthcare spending tends to be lower on average than when the young are a minority. Moreover, when the old are a majority the equilibrium public healthcare provision depends critically upon the extent of income inequality. We also discuss implications regarding the on-going demographic transition (population ageing) and the Covid-19 pandemic.
Keywords: D72; H42; I14; 330; Demography; Economic Inequality; Healthcare; Voting